Governance, compliance, and digital transformation: Pathways to sustainable people’s credit funds in Vietnam - Nguyen, Dieu Linh; Phan, Dang Hai; Le, Tra Thi Huong; Truong, Quoc Cuong; Nguyen, Bao Huyen (Edelweiss Applied Science and Technology, 2026)
This study investigates the critical factors influencing the sustainability of People's Credit Funds (PCFs) in Vietnam, which are vital cooperative institutions for promoting financial inclusion in rural areas. Utilizing structural equation modeling (SEM) and survey data collected from 202 PCF employees across Northern, Central, and Southern Vietnam, the research assesses the impact of Governance Structure, Strategic Planning, Financial Compliance, and Information Management on institutional sustainability. The findings reveal that Financial Compliance has the most significant influence on PCF sustainability, followed by Information Management. Governance Structure and Strategic Planning also demonstrate positive, albeit smaller, significant effects. Notably, Information Management is found to partially mediate the relationship between Governance Structure and institutional sustainability, adding depth to the understanding of these interconnections. Based on these results, the study recommends that PCFs adopt International Financial Reporting Standards for Small and Medium Enterprises (IFRS for SMEs), invest in digital platforms, standardize governance practices, and implement risk-based strategic planning. These findings not only contribute to the existing microfinance literature but also offer practical, actionable insights for policymakers to enhance the resilience and effectiveness of PCFs in Vietnam's transitional economy.